Clustering-triggered emission of EPS-605 nanoparticles and their application in biosensing - Li, Chengcheng (2023)
Natural carbohydrates with intrinsic luminescent properties have drawn increasing attention thanks to their fundamental importance and promising applications. To expand the range of natural nonconventional biomacromolecule luminogens and to gain deep insights into their emission mechanism, we prepared EPS-605, a naturally occurring spherical nanoparticle based on negatively charged exopolysaccharides (EPS), and studied its emission behavior. It was found that EPS-605 was highly emissive in the aggregate state, such as powder and film. Furthermore, EPS-605 aqueous solutions exhibited concentration-enhanced emission characteristics. According to fluorescence spectra and confocal images, the fluorescence phenomenon of EPS-605 was not affected by the pH value and the carbon sources. The emission behavior of EPS-605 was attributed to the clustering-triggered emission (CTE) mechanism. Moreover, EPS-605 was successfully utilized for Fe3+ detection since its fluorescence could be selectively quenched by Fe3+. It could be used to detect Fe3+ with a low limit of detection (0.06 μM) and a wide detection range from 0.05 to 250 μM. Overall, these findings not only benefit the exploitation of EPS-based nonconventional biomacromolecule luminogens, but also reveal the potential applications of EPS-605 in biosensing/bioimaging, anticounterfeiting, and encryption owing to its excellent biocompatibility, environmental friendliness, and intrinsic photoluminescence property.